2009
DOI: 10.1080/00365520802495560
|View full text |Cite
|
Sign up to set email alerts
|

Possible regulation of genes associated with intracellular signaling cascade in rat liver regeneration

Abstract: ObjectiveThe importance of signal transduction in cell activities has been generally accepted. The purpose of this study was to analyze the regulatory effect of intracellular signaling cascade-associated genes on rat liver regeneration (LR) at transcriptional level.Material and methodsThe associated genes were originally obtained through a search of the databases and related scientific publications; their expression profiles were then checked in rat LR using the Rat Genome 230 2.0 array. The LR-associated gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Though the role played by angiotensinogen (AGT) after PH is not well known, it was reported to peak at 6th hour after PH and to maintain its expression up to 24 hours (25). Xu et al revealed a 5-fold increase of AGT expression (37). This is consistent with our fi nding showing a 5-fold increase of AGT in the Group II than that in the Group I.…”
Section: Discussionsupporting
confidence: 93%
“…Though the role played by angiotensinogen (AGT) after PH is not well known, it was reported to peak at 6th hour after PH and to maintain its expression up to 24 hours (25). Xu et al revealed a 5-fold increase of AGT expression (37). This is consistent with our fi nding showing a 5-fold increase of AGT in the Group II than that in the Group I.…”
Section: Discussionsupporting
confidence: 93%
“…29 The regulation of genes associated with intracellular signaling cascades is highly suspected to be involved in the mechanism of liver regeneration. 30 The ratio of remnant liver weight to body weight increased to near 90% of the original liver weight at 72 h after PH. As shown by the BrdU proliferation ELISA assay, proliferation of the isolated hepatocytes was markedly induced by PH on day 3 and day 4.…”
Section: Discussionmentioning
confidence: 98%
“…Inhibitors and monoclonal antibodies can target the EGFR and TGF-β signaling pathways in breast cancer therapy 22. Small GTPase-mediated signal transduction can stimulate the immune response, control cell replication, play a role in cytoskeletal reconstruction and cell migration, and participate in protein transport 23. In the KEGG pathway analysis, the coexpressed genes were mainly enriched in BC, the calcium signaling pathway, the cAMP signaling pathway, the GnRH signaling pathway, arachidonic acid metabolism and the Rap1 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%